Anti-Salmonella activity of pyruvic and succinic acid in combination with oregano essential oil. (April 2020) - Mohan, Anand; Purohit, Anuj S.
Abstract: This study was designed to assess the anti- Salmonella efficiency of pyruvic (PA) and succinic acid (SA) with or without oregano essential oil (EO) in different model systems. Three model systems were designed: 1). Salmonella Typhimurium (ST) cell in suspensions; 2). Cultured ST cells artificially inoculated on raw chicken; and 3). ST cells attached to stainless steel (SS) coupon. Minimum inhibitory concentration (MIC) and minimum bacterial concentration (MBC) for ST population was determined using macro-dilution assays. Results of the assays showed MBC of 0.5% (w/v) PA, 3% (w/v) SA, and 0.04% (v/v) for EO. For combinations of organic acid and EO, the MBC was: PA + EO (0.25 & 0.02%), and SA + EO (0.25 + 0.02%) respectively. Maximum Salmonella reduction obtained in cells inoculated on chicken skin was 1.4 log CFU/cm 2 with 1% PA + 0.08% EO combination and 1.0 log10 CFU/cm 2 with 6% SA + 0.08% EO combination. Approximately 6.0 log10 CFU/coupon of attached Salmonella cells (48 h) were inactivated after a 5 min exposure with 0.25% PA + 0.02% EO, and 1.5% SA + 0.02% EO. The combinations of PA + EO and SA + EO both exhibited strong anti- Salmonella activity in cell suspensions, on cells attached to stainless steel, and were effective in reducing Salmonella inoculated on raw chicken. Findings of this study suggest that PA or SA with or without EO are potent antimicrobials in reducing ST populations and merit further research for raw poultry, meat, and other sanitation applications. Highlights: Anti- Salmonella activity of pyruvic (PA), succinic acid (SA) with essential oil (EO) was evaluated. 0.25% PA+0.02% EO and 0.25% SA+0.02% EO inactivated >5 log CFU/ml Salmonella in <10 s. 1% PA+0.08% EO and 6% SA+0.08% EO reduced >1 log CFU/cm 2 Salmonella on raw chicken. 0.25% PA+0.02% EO and 1.5% SA+0.02% EO inactivated Salmonella 48 h attached on stainless steel.